Pengaruh Model Pembelajaran Meaningful Instructional Design (MID) terhadap Keterampilan Menulis untuk Teks Laporan Hasil Observasi dari Siswa Sekolah Menengah Pertama - Tanjung, Yessi; Lubis, M. Joharis (Jurnal Bahasa dan Sastra, 2024)
Based on observations conducted by the researcher at the junior high school level in Sitinjo, it was found that a majority of students face difficulties in comprehending the material on writing observation report texts. This study aims to determine the impact of the Meaningful Instructional Design (MID) model on the writing skills of seventh-grade students in relation to observation report texts. The population for this study consists of all seventh-grade students at a junior high school in Sitinjo, totaling 147 individuals. The sample for this study includes 31 students from class VII-1. The research method employed is an experimental method with a one-group pretest-posttest design. The data analysis techniques utilized include requirement testing, normality testing, and hypothesis testing. The average post-test score of 84.65 falls into the good category, while the average pre-test score of 64.84 is classified as fair. Based on the research results (pretest and posttest) and the "t" test results, where t_calculated > t_table (8.224 > 2.04523), the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. The study findings indicate that the utilization of the Meaningful Instructional Design (MID) model has a positive influence on the writing skills of seventh-grade students regarding observation report texts at a junior high school in Sitinjo during the 2023/2024 academic year.